The Use of Epoetin-α in Revision Knee Arthroplasty - Lawrence A. Delasotta; Ashwin V. Rangavajjula; Michael L. Frank; Jamie L. Blair; Fabio R. Orozco; Alvin C. Ong (Advances in Orthopedics)
Introduction. To evaluate the efficacy of epoetin-α prior to revision total knee arthroplasty, we hypothesized that epoetin-α will reduce blood transfusion. Methods. Eighty-one patients were compared in this retrospective review; twenty-eight patients received our dosing regimen. All patients were mildly anemic. Epoetin-α to control (1 : 2) patient matching occurred so that one of two attending surgeons, gender, BMI, complexity of surgery, ASA score, and age were similar between groups. The clinical triggers for blood transfusion during or after the procedure were determined based on peri- and postoperative hemoglobin levels, ASA score, and/or clinical symptoms consistent with anemia. Blood salvage was not used. Results. Blood transfusion and length of stay were lower in the study group. None of the patients who received epoetin-α underwent transfusion. Hemoglobin increased from 11.97 to 13.8, preoperatively. Hemoglobin at day of surgery and time of discharge were higher. Gender, BMI, ASA score, total and hidden blood losses, calculated blood loss, preop PLT, PT, PTT, and INR were similar between groups. One Epogen patient had an uncomplicated DVT (3.6%). Conclusions. Epoetin-α may have a role in the mildly anemic revision knee patient. It may also decrease patient length of stay allowing for earlier readiness to resume normal activities and/or meet short-term milestones. A randomized study to evaluate the direct and indirect costs of such a treatment methodology in the mildly anemic revision patient may be warranted.